CARA-CARA NICA MEMPENGARUHI RAKYAT SUPAYA TIDAK BERSIMPATI KEPADA PARA PEJUANG PADA MASA REVOLUSI FISIK DI BALI 1945-1950 - Ida Bagus Astika Pidada (Universitas Warmadewa, 2019)
[Title: The Ways of Influencing the People of NICA to Understand at Physical Revolution for Balinese People in Bali 1945-1950] Giving up without the conditions of Lieutenant General H. Ter Pooerten (Commander of the Dutch East Indies) to Lieutenant General Hitosyi Imamura (Japanese Army Chief), then the Dutch East Indies government has since ended in Indonesia. Not a long time ago Japan ruled in Indonesia, on August 15th, 1945 surrendered unconditionally to the allies. Then on March 2nd, 1946 the Y Brigade began landed along the Sanur coast. This Y Brigade is nicknamed